THE UTILIZATION OF GEOTHERMAL SILICA WASTE IN ADDITIVE MANUFACTURING WITH STEREOLITHOGRAPHY RESIN FOR DETAILED PROTOTYPING PROCESS - Tanbar, Fefria; Darmawan, Muhammad Rakhadzaky Indra; Wibisono, Muhammad Maheswara; Ariyadi, Hifni Muchtar; Nugraha, Ariyana Dwiputra; Wiranata, Ardi; Muflikhun, Muhammad Akhsin (International Journal of Mechanical Engineering Technologies and Applications, 2025)
Silica deposit powder from geothermal waste often becomes material waste that difficult to utilize and re-use. The characterization of silica deposit powder has a significant part in understanding its structure, composition, and potential application. Using silica as a filler system in additive manufacturing is one of the processes that can utilize silica deposit powder. This material has the potential to be used to create prototype product with stereolithography resin for 3D printing. The present study discusses the ability to mix specimens of silica (size 600 microns) and resin with a composition ratio of 1:100. The turbidity test revealed that the specimen mixed in the resin contents showing after 30- and 40-minutes examination from spectrophotometer. In the hardness test, by adding filler materials, it is shown that the filler decreased the hardness more than 46%. This research also successfully examines the most effective particle sizes to the length of time required for the mixing and curing processes in order to obtain the most optimal results.